Anthropogenic debris accumulation in the Argentine deep sea: evidence of an irreversible sink - Maialen G. Ardusso; Florencia B. Rial; Melisa D. Fernández Severini; Ele Beruschi; Luana Y. Acosta; Andrea N. Álvarez; Juan Cruz Carbajal; Danya Awshah; Xenia Barnes; Lucia Chesta; Moira Décima; Brenda Doti; et al. (Frontiers in Marine Science, 2026)
The seafloor is recognized as a major sink for marine debris, while deep-sea litter remains poorly investigated due to the logistical and economic constraints associated with seabed exploration. This study reports for the first time the occurrence of marine debris found on the Argentine deep seafloor using the SOI’s Remotely Operated Vehicle (ROV), providing the first documented evidence for this region. A total of 29 litter items were recorded across 55.6 km of surveyed seafloor. The highest debris abundance was recorded in submarine canyon areas (1.4 items/km), whereas the Malvinas Basin showed the lowest levels (0.1 items/km), likely associated with hydrodynamic conditions. In addition, plastic items, fishing ropes, and nets were the most frequently recorded types of debris. These findings establish a baseline of the current status of deep-sea marine debris and propose future directions for the region.